2010
DOI: 10.3201/eid1611.100628
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotropism of Merkel Cell Polyomavirus Infection, Nova Scotia, Canada

Abstract: Lymphoid cells may be a site for virus persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
(29 reference statements)
3
36
0
1
Order By: Relevance
“…These results are consistent with a previous serologic study from Tolstov and colleagues (20) on 18 CLL cases where they found no median differences when compared with 18 acute lymphoblastic leukemia subjects. Our serologic data are also in agreement with previous studies where almost null viral DNA and/or antigen were detected (13)(14)(15)(16)). An exception to the above is a report from Pantulu and colleagues (17) and complemented by Haugg and colleagues (18) describing the detection of DNA encoding a mutated MCV LT-Ag in CLL cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with a previous serologic study from Tolstov and colleagues (20) on 18 CLL cases where they found no median differences when compared with 18 acute lymphoblastic leukemia subjects. Our serologic data are also in agreement with previous studies where almost null viral DNA and/or antigen were detected (13)(14)(15)(16)). An exception to the above is a report from Pantulu and colleagues (17) and complemented by Haugg and colleagues (18) describing the detection of DNA encoding a mutated MCV LT-Ag in CLL cells.…”
Section: Discussionsupporting
confidence: 93%
“…Among subjects with lymphoproliferative disorders, CLL subjects have been shown to have higher MCV DNA detection rates, although prevalences and viral load are low (13)(14)(15)(16). LT-Ag detection is almost null in lymphomas but in purified CD5þ/CD19þ CLL cells a mutated DNA sequence encoding for MCV LT-Ag has been reported (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, autopsy brain tissue samples of HIV-positive patients with KIPyV/WUPyV reactivation were examined. No specific histopathological lesions were found associated with the presence of KIPyV and WUPyV (41) unlike MCPyV (8,42).…”
Section: Histopathologymentioning
confidence: 99%
“…The primary target cells and the host cells that can function as reservoir are not known, but the virus seems to be common in healthy skin, skin lesions, eyebrow hairs, and warts, indicating a dermatotropism of this virus [Wieland et al, 2009;van der Meijden et al, 2010;Mertz et al, 2010a;Faust et al, 2011;Wieland et al, 2011]. MCPyV DNA is also found in blood, gall bladder, appendix, liver, lung, lymphoid, and intestine tissue [Feng et al, 2008;Sharp et al, 2009;Goh et al, 2009;Shuda et al, 2009;Foulongne et al, 2010a;Husseiny et al, 2010;Loyo et al, 2010;Toracchio et al, 2010;Campello et al, 2011;Pancaldi et al, 2011;reviewed in Moens et al, 2010 and. Another study has suggested that MCPyV may persist in and spread through inflammatory monocytes [Mertz et al, 2010b].…”
Section: Mcpyv: Route Of Infection Cell Tropism and Transmissionmentioning
confidence: 99%